Towards a discourse for criticism in language teaching: analysis of sociocultural representations in mass media (2010)
This article states that in order to exercise citizenship with responsibility, language teachers need to popularize a discourse for criticism in which students and teachers transcend tacit knowledge and common sense due to meta-cognition and argumentation and reach systematic knowledge and procedures posed by experts in the different disciplines. As illustrated inside, the source and objective of analysis by means of which this discourse can be contextualized in language teaching is the language of mass media and all the sociocultural and signifying practices that it invokes. We conclude that through the analysis of mass media it is possible to educate students with the basic knowledge and skills necessary to interact critically in the world. El artículo plantea que, con el propósito de ejercer su ciudadanía, los maestros de lenguas deben popularizar un discurso para la crítica en el cual los estudiantes y los profesores trasciendan el conocimiento tácito y el sentido común mediante la argumentación y la metacognición, y alcancen conocimiento y procedimientos sistemáticos planteados por expertos en las diferentes disciplinas. Como se ilustra en el texto, la fuente y objeto de análisis mediante el cual se contextualiza este discurso en la enseñanza de la lengua es el lenguaje de los medios de comunicación y las prácticas socioculturales y de significación que este provoca. Concluimos que a través del análisis de los medios es posible educar a los estudiantes con conocimientos y habilidades básicas necesarias para interactuar en el mundo.